Hojuelas glaseadas a partir de harina de Xanthosoma sagittifolium (papa huitina) libre de gluten - Coral Miguel, Georgette Michelle (2019)
This research was made with the objective of determinate the technology for the elaboration of Xanthosoma Sagittifolium (Huitina Potato) gluten free glassed flakes. It is an alternative of alimentation specifically named “breakfast cereal”. Food drying by plates, an experimental design was applied in a 55°C for 10 hours parameter. (Chirinos et. al, 2001), huitina flour contains 5.22 total fiber, 17% vitamin C, 6.3mg of iron, 62.5mg of calcium, 290mg of phosphorus, 220.4mg of potassium, 0.02mg of copper and 0.03mg of zinc. For the flakes’ elaboration an experimental design of two factors was used, F1: 20%, 25% and 30% of Huitina flour concentration respectively. F2: Time and temperature. Nutritional value of gluten free Xanthosoma Sagittifolium (Huitina Potato) glassed flakes as a result has 16.81mg of calcium, 2.8mg of iron, 1.56% protein, 9.5mg of vitamin C, 0.50% fiber, 120mg of phosphorus, 0.13mg of zinc. Microbiologic analysis of Huitina flakes indicates it being inside the permissible limits according to Sanitary Norm for Food Fabrication from Grain and others, destined to social alimentation programs (451-2006/MINSA) indicating well hygiene in the manufacturing of the product and being able for human consumption.